Heterogeneously Integrated Graphene/Silicon/Halide Waveguide Photodetectors toward Chip-Scale Zero-Bias Long-Wave Infrared Spectroscopic Sensing - Ma, Yiming (AMER CHEMICAL SOC, 2022)
10.1021/acsnano.1c01859